Fist of the North Star. Volume 7 - Buronson, 1947- (Viz signature., 2022)
"In the original classic manga set in a postapocalyptic wasteland ruled by savage gangs, a hero appears to bring justice to the guilty. This warrior named Ken holds the deadly secrets of a mysterious martial art known as Hokuto Shinken--the Divine Fist of the North Star! In a postapocalyptic world, humanity has risen from the ashes of all-out nuclear war to a nightmare of endless suffering. It is a time of chaos. Warlords and gangs of savage marauders rule the broken ruins of civilization, terrorizing and enslaving the survivors. Life has become a brutal struggle for existence and death the only release. The masters of the Nanto Seiken school are known as the Nanto Rokuseiken--the Six Holy Fists of the South Star. Of the six, the most powerful is Holy Emperor Souther. But Shu, another warrior of Nanto Seiken, dares to resist Souther's tyranny. Shu once saved Kenshiro's life. Now the two will team up again. But Kenshiro is unaware of Souther's secret--a secret so powerful even Raoh won't dare challenge his reign..."--provided by publisher.